Surface functionalization of plasticized chitosan films through PNIPAM grafting via UV and plasma graft polymerization. (August 2018) - Conzatti, G.; Chamary, S.; De Geyter, N.; Cavalie, S.; Morent, R.; Tourrette, A.
Graphical abstract: Highlights: Chitosan were blended with PEG and glycerol to improve films mechanical properties. PNIPAM was then graft polymerized on chitosan films through UV or plasma treatments. Thermosensitiveness of the resulting films was then evaluated. Both UV and plasma treated films showed stimuli responsive surfaces. Abstract: Chitosan films were formulated and subsequently given thermosensitive properties by modifying the surfaces. The first step involved the incorporation of poly(ethylene glycol) (PEG) plasticizers at various ratios into the chitosan blends. Tensile tests showed that the molecular weight of the PEG impacted the mechanical properties, while the plasticizing effect was optimal for a PEG content of 20%. The addition of glycerol, in combination with PEG, increased the elongation at break without altering the tensile strength. In order to add thermosensitive properties to the chitosan films, poly(N-isopropylacrylamide) (PNIPAM) was graft polymerized on the surface via two methods: UV irradiation or plasma treatment. The surface modification was evaluated in terms of surface characteristics (XPS, SEM, contact angle) and bulk swelling abilities, with a specific focus on the thermosensitive nature due to the lower critical solution temperature (LCST) transition of the PNIPAM. The two grafting methods implied differences in terms of thermal responsiveness. Indeed, due to the presence of particles on their surfaces, UV grafted samples exhibited higher hydrophilicity and thermosensitivity, whereas their lower content of PNIPAM involved lower swelling thermal dependence. All of these results support the interest in PNIPAM grafted chitosan surfaces for the development of smart biomaterials.